2023
DOI: 10.1177/10711007231198429
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity Score Matched Exploration of Infection in Primary Total Ankle Arthroplasty

Albert T. Anastasio,
Kevin A. Wu,
Billy I. Kim
et al.

Abstract: Background: Infection is a serious complication of primary total ankle arthroplasty (TAA) and can lead to implant failure and revision surgery. Various demographic, comorbidity, and surgical factors have been associated with an increased risk of infection. However, the evidence base remains limited, and further research is needed regarding infection in TAA. This study aims to analyze risk factors of infection and explore outcomes following infected TAA. Methods: A retrospective cohort study was conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These cohorts were propensity score matched for covariates of age, gender, and Charlson comorbidity index (CCI), which include variables that have been identified as risk factors for complications after TAA. 1 Propensity score matching was performed in a 4:1 ratio (controls/study) using the nearestneighbor method and a caliper width of 0.1, as described in prior literature. 1 Hindfoot arthrodesis for this study was defined as either subtalar or triple arthrodesis.…”
Section: Study Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cohorts were propensity score matched for covariates of age, gender, and Charlson comorbidity index (CCI), which include variables that have been identified as risk factors for complications after TAA. 1 Propensity score matching was performed in a 4:1 ratio (controls/study) using the nearestneighbor method and a caliper width of 0.1, as described in prior literature. 1 Hindfoot arthrodesis for this study was defined as either subtalar or triple arthrodesis.…”
Section: Study Cohortsmentioning
confidence: 99%
“…1 Propensity score matching was performed in a 4:1 ratio (controls/study) using the nearestneighbor method and a caliper width of 0.1, as described in prior literature. 1 Hindfoot arthrodesis for this study was defined as either subtalar or triple arthrodesis. The PearlDiver database does not allow for discernment of talonavicular or calcaneocuboid arthrodesis as there is no specific CPT code for those fusions.…”
Section: Study Cohortsmentioning
confidence: 99%
“…Looking at infection in primary TAAs, Anastasio et al 3 performed a Level III case-control study of 1863 TAAs, 19 of which were diagnosed with an infection. The identifiable overall infection rate was 1.0%.…”
Section: Total Ankle Arthroplastymentioning
confidence: 99%
“…Research investigating the use of BMI as a surrogate for risk stratification in primary TAA has not been unifom. 2 , 6 , 17 , 19 , 29 , 39 A database study found that the incidence of TAA failure was higher in individuals classified as obese (BMI ≥ 30) compared to those with a normal BMI. 39 However, recent retrospective studies have demonstrated that obesity was not associated with increased rates of complications after primary TAA 17 and BMI was not a risk factor of implant failure.…”
Section: Introductionmentioning
confidence: 99%